2016
DOI: 10.1042/bst20160073
|View full text |Cite
|
Sign up to set email alerts
|

‘Nothing of chemistry disappears in biology’: the Top 30 damage-prone endogenous metabolites

Abstract: Many common metabolites are intrinsically unstable and reactive, and hence prone to chemical (i.e. non-enzymatic) damage in vivo Although this fact is widely recognized, the purely chemical side-reactions of metabolic intermediates can be surprisingly hard to track down in the literature and are often treated in an unprioritized case-by-case way. Moreover, spontaneous chemical side-reactions tend to be overshadowed today by side-reactions mediated by promiscuous ('sloppy') enzymes even though chemical damage t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 58 publications
0
76
1
Order By: Relevance
“…In addition, it 412 has been shown that growth of the primary root of Arabidopsis is significantly reduced in 413 amiPDX1.2 lines when exposed to heat stress, corroborating that PDX1.2 is requisite for sustaining 414 normal development under environmentally stressful conditions The need for vitamin B 6 under heat stress conditions 418 As alluded to above, B 6 vitamers, in particular the cofactor form PLP (and notably the product of 419 PDX1), by its very nature of being highly reactive, is also very chemically labile and thus prone to 420 destruction by the damaging oxidative conditions that ensue upon environmental stress (Linster et 421 al., 2013). Indeed, PLP recently made it into the compiled top 30 chart of damage prone 422 endogenous metabolites (Lerma-Ortiz et al, 2016). In particular, while the reactive aldehyde group 423 of PLP (essential for cofactor function) can undergo oxidation or condensation with the ε-amino 424 group of lysine, it can also react with the amino group of other compounds that may accumulate 425 under stress conditions, rendering the compound useless as a cofactor.…”
Section: Discussion 339mentioning
confidence: 99%
“…In addition, it 412 has been shown that growth of the primary root of Arabidopsis is significantly reduced in 413 amiPDX1.2 lines when exposed to heat stress, corroborating that PDX1.2 is requisite for sustaining 414 normal development under environmentally stressful conditions The need for vitamin B 6 under heat stress conditions 418 As alluded to above, B 6 vitamers, in particular the cofactor form PLP (and notably the product of 419 PDX1), by its very nature of being highly reactive, is also very chemically labile and thus prone to 420 destruction by the damaging oxidative conditions that ensue upon environmental stress (Linster et 421 al., 2013). Indeed, PLP recently made it into the compiled top 30 chart of damage prone 422 endogenous metabolites (Lerma-Ortiz et al, 2016). In particular, while the reactive aldehyde group 423 of PLP (essential for cofactor function) can undergo oxidation or condensation with the ε-amino 424 group of lysine, it can also react with the amino group of other compounds that may accumulate 425 under stress conditions, rendering the compound useless as a cofactor.…”
Section: Discussion 339mentioning
confidence: 99%
“…Figure 1 uses color-coded arrows to show the site and nature of damage reactions that vitamins and cofactors can undergo in physiological conditions, and Table I catalogs the reactions corresponding to the arrows. Note that Figure 1 is bristling with arrows, which helps explain why most of the B vitamins/cofactors made it into a "Top 30" list of damage-prone metabolites (Lerma-Ortiz et al, 2016) and why all organisms have dedicated systems to deal with vitamin/cofactor damage (Linster et al, 2013). "Bad things happen" to B vitamins and cofactors because these compounds are basically chemical and metabolic "accidents waiting to happen."…”
Section: Chemical and Metabolic Lability: Why Bad Things Happen To Gomentioning
confidence: 99%
“…Some decomposition products could be genotoxic. Alternatively, metabolites alterations by chemical side reactions are widespread (Lerma-Ortiz et al, 2016). Dihydropyrimidines may react with oxidants or other metabolites to form potent DNA damaging agents (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%